"Fractured Resemblances": Contested Multinational Heritage and Soft Power. Issue 1 (February 2020) - Sargent, Sarah
Abstract: Intangible cultural heritage elements are shared across state borders. In many instances, states join in multinational nominations to inscribe the heritage element in a way that reflects this reality. But, at times, states are unwilling or unable to cooperate in a mutual nomination that reflects the shared nature of the heritage element. The consequence of this is that heritage elements can then be nominated by individual states without any reflection of the multinational or cross-border nature of the element; thus leaving the heritage elements shorn of this aspect of their nature. The current international heritage legal regime, through the United Nations Educational, Scientific and Cultural Organization, does not adequately acknowledge or address this problem. This article, through a case study of the successful nomination by Azerbaijan of the horseback game of chovqan, examines the causes and consequences of these "fractured resemblances." It analyzes the links between cultural heritage, conflict, and the use of heritage as a form of soft power. It focuses on the use of single-state inscription as a soft-power means of obtaining international prestige and support and the resultant effects on shared cultural heritage elements. From this, suggestions for changes to international heritage laws for the inscription of cultural heritage are suggested to accommodate the reality of the connection between cultural heritage, conflict, and power and to avoid the occurrence of "fractured resemblances" of heritage shared across state lines.